2019 IEEE International Symposium on Technologies for Homeland Security (HST) 2019
DOI: 10.1109/hst47167.2019.9032931
|View full text |Cite
|
Sign up to set email alerts
|

Detecting, identifying, and localizing radiological material in urban environments using scan statistics

Abstract: A method is proposed, based on scan statistics, to detect, identify, and localize illicit radiological material using mobile sensors in an urban environment. Our method handles varying levels of background radiation that change according to an (unknown) environment. Our method can accurately determine if a source is present along a street segment as well as identify which of six possible sources generated the radiation. Our method can also localize the source, when detected, to within a few seconds. We have pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…Interest in this research area is demonstrated by the Detecting Radiological Threats in Urban Environments challenge set in 2019 by the US National Nuclear Security Administration (NNSA), with a prize pool of $100,000 [99]. Using Monte Carlo methods, the NNSA simulated a single 5.08 × 10.16 × 40.64 cm NaI(Tl) detector moving through model urban environments containing different sources such as HEU, WGPu, 131 I, 60 Co or 99m Tc, asking research teams to design detection algorithms to identify the presence of sources, identify the isotopes and locate the point of closest approach of the detector [99,100]. A further demonstration of the interest in mobile detector networks is the USA Defence Advanced Research Projects Agency's (DARPA) SIGMA project in which over 1000 portable radiation detectors were used to map an urban area in Washington, D.C. [101,102].…”
Section: Mobile Detector Networkmentioning
confidence: 99%
“…Interest in this research area is demonstrated by the Detecting Radiological Threats in Urban Environments challenge set in 2019 by the US National Nuclear Security Administration (NNSA), with a prize pool of $100,000 [99]. Using Monte Carlo methods, the NNSA simulated a single 5.08 × 10.16 × 40.64 cm NaI(Tl) detector moving through model urban environments containing different sources such as HEU, WGPu, 131 I, 60 Co or 99m Tc, asking research teams to design detection algorithms to identify the presence of sources, identify the isotopes and locate the point of closest approach of the detector [99,100]. A further demonstration of the interest in mobile detector networks is the USA Defence Advanced Research Projects Agency's (DARPA) SIGMA project in which over 1000 portable radiation detectors were used to map an urban area in Washington, D.C. [101,102].…”
Section: Mobile Detector Networkmentioning
confidence: 99%
“…Technological tools are nowadays a means for the automatic detection of biohazards [1], [2] as well as for the analysis of waste such as plastic paper or metal that may involve the same type of risk [3]. Identifying, locating, and detecting biohazards is of utmost importance to safeguard human lives [4]. Among these identification methods, those based on deep learning stand out, for example, employed in [5] to detect plastic waste in rivers and in [6] to develop an intelligent waste management system, both based on deep learning through convolutional networks (CNN) [7], which extends to the detection of biological risks [8].…”
Section: Introductionmentioning
confidence: 99%